Relationships Between Adolescents’ Psychological Well-Being and Problem Behavior in Theft Cases in Youth Correctional Center Bandung - Firdasannah, Astri; Ramanda Justice, Widi; Amanda Suherman, Nazwa (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
This study aims to determine the relationship between adolescents’ psychological well-being and problem behavior in children in conflict with the law (ABH) in theft cases in the Youth Correctional Center (YCC) Bandung. This research is preliminary to the development of a family function therapy design. The quantitative correlational approach is the research methodology employed in this study. Quota sampling was the sampling method employed. In incidents of theft, the study's sample quota was 36 (ABH). The Difficulty and Strength Questionnaire (KKA) measuring instrument was used to determine the level of difficulty and strength they experienced. Adolescent psychological well-being was measured using the Brief Scale of Psychological Well-Being for Adolescents (BSPWB-A)—Indonesian Version. The method of analysis used for the product-moment Pearson correlation test is the source of the data. The result of this study shows a significant negative correlation between adolescents’ psychological well-being and problem behavior in children in conflict with the law (ABH) in theft cases in YCC Bandung (r = -0.200; p < 0.05). The hypothesis proposed is accepted. The implications of this study are the basis for the development of family functional therapy, which considers adolescents’ psychological well-being as part of family functional therapy to reduce their problematic behavior.